Constitutional presumption of innocence and the institution of release from criminal liability: correlation issues - Ярослав Ступник; Марина Ступник (Конституційно-правові академічні студії, 2024)
The purpose of the article is to determine, taking into account the results of the analysis of the current legislation of Ukraine and the provisions of the doctrine of criminal law, the issues of correlation and ensuring the compliance of the institution of release from criminal liability with the constitutional presumption of innocence.